RANCANG BANGUN SISTEM PENGAJUAN BIMBINGAN REKOGNISI PEMBELAJARAN LAMPAU (RPL) PADA PROGRAM PROFESI INSINYUR UNIVERSITAS UDAYANA - Ni Ketut Relawati; Ida Ayu Putu Febri Imawati; I Nyoman Bagus Suweta (Jurnal Manajemen dan Teknologi Informasi, 2024)
Recognition of Past Learning (RPL) is recognition of a person's learning achievements obtained from formal, non-formal, informal education, and/or work experience as a basis for continuing formal education and for equivalency with certain qualifications. Udayana University which is located at JL. PB. Sudirman Denpasar is one of the universities that carries out the Ministry of Research, Technology and Higher Education's mandate to organize the Professional Engineer Program. There are two delivery routes for the Professional Engineer Program, namely the Regular Route and Recognition of Past Learning (RPL). The RPL process in the Udayana University Professional Engineer Program still uses manual data processing, where PPI study program operators still record manually the number of students who have been tutored and the number of students who have submitted exam applications, so it takes a long time and slows down the RPL process. Therefore, it is necessary to design an information system for submitting RPL guidance in the Udayana University Professional Engineer Program. It is hoped that this Information System Design will simplify and speed up the RPL process in the Udayana University Professional Engineer Program.